Globalisasi Hukum dalam Pluralisme Hukum Modern - Irianto, Sulistyowati (UI Scholars Hub, 2025)
This article revisits the concept of legal pluralism, which continues to evolve alongside society and all its complexities. Knowledge of legal pluralism evolves in line with societal changes identified through scientific research and activities. Over the past two decades, developments have drawn attention to the globalisation of law, leading to the concept of modern legal pluralism. The intertwining and mutual influences, as well as the adoptions and reproductions, resulting from encounters between legal systems have become increasingly complex due to the presence of international and transnational law. This is particularly significant in the areas of human rights, democracy, clean governance and environmental crisis. Today, global citizens are connected to one another because they share knowledge about legal norms and values brought about by 'new law'. The study of modern legal pluralism has methodological consequences which provide new opportunities for researchers. Explaining legal pluralism simply by mapping its coexistence as entities with clearly defined boundaries is no longer viable. Researchers now have a golden opportunity to reconstruct events in a multi-spatial manner, transcending the boundaries of space and time.